Lei nº 11.638/07 e as dificuldades enfrentadas pelas cooperativas agropecuárias da região oeste do Paraná - Koike, Ana Luiza; Meira, Rosane de; Rovaris, Nicole Regina Souza; Sandri, Emanuel Campigotto (Revista de Gestão e Organizações Cooperativas, 2019)
The main objective of this study was to identify the greatest difficulties and facilities of agricultural cooperatives in the western region of the state of Paraná when implementing Law 11,638 / 07. Regarding the objectives, the study is characterized by a descriptive research, regarding the procedures a field research and the approach to the problem, a qualitative research. The data collection instrument used in the survey was the questionnaire, where 4 (four) cooperative accountants answered questions about Law 11,638 / 07 and their applicability to cooperativism, which were applied between September 30 and October 8. The study made it possible to verify that Cooperatives do not fully agree on the internationalization of Brazilian standards, but that both believe that most of the requirements brought by law are important for the accounting sector of cooperatives. They differ as to the importance of Law No. 11,638 / 07 for cooperativism, since half the accountants believe that it was of great importance and the other half, which did not affect cooperativism. It is concluded that the implementation of Law 11,638 / 07 was considered an activity not very complex for the professionals of the accounting sector of the agricultural cooperatives of western Paraná.